Avicultura de corte comercial na Ilha do Maranhão: perfil socioeconômico, produtivo e utilização de cama de aviário - Dias Filho, Aymoré Fernandes (2018)
The objective of this research was to characterize the socioeconomic and productive profile of commercial poultry in the Island of Maranhão - MA and to report the sanitary episode of avian litter intake by cattle, epidemiologically characterizing the sanitary situation and the sanitation measures implemented. In order to reach the objectives of this study, 10 commercial broiler breeders registered at the State Agency of Agricultural and Livestock Defense of the State of Maranhão were interviewed through semi-structured questionnaires. E, used 119 cattle from a rural property located in the municipality of São José de Ribamar - MA. As a basic research instrument (questionnaires) it was possible to determine some characteristics of poultry farming, such as: profile of poultry producers; characteristics of properties; performance of the activity; and, production, use and marketing of aviary bed. With the results obtained in this study we observed a new organization of the production chain of broilers in the study area. Thus, there is a producer with a differentiated profile in the Island of Maranhão, characterized by production in partnership with integrating companies and employment of hired labor, characterizing an industrial-type poultry; incorporation of producers with larger land areas and greater bird housing capacity; and, the presence of technical assistance that is reverted in improvement of the sanitary state and, consequently, in the indicators of productive performance. As for the sanitary episode, this was the result of an anonymous complaint about the supply of poultry litter as feed for cattle. After 72 hours of the complaint, property inspection and collection of feed samples were carried out. The collected material was sent to the National Agricultural Laboratory of Santa Catarina for the detection or not of by-products of animal origin. In the initial inspection to the rural property was verified the presence of aviary bed supplied to the cattle as food. And, the laboratory result was detected the presence of uncalcined bones, non-hydrolyzed feathers and blood, which proves the feeding of the animals with byproducts of animal origin. The data obtained in this study show that commercial poultry farming in the Island of Maranhão has great potential for expansion, mainly based on grain supply, climate, favorable topography and good infrastructure. However, there is a need to establish incentive measures for poultry farms focused on health education, taking into account the production, use and commercialization of poultry litter and the risks arising from them in ruminant feeding. It is suggested the intensification in the active inspections in ruminant rearing properties and the control in the transit of the aviary bed that appears in the documentation the purpose of use of this byproduct.